Zależność w analizie danych - dyskusja nad niektórymi podejściami - Jajuga, Krzysztof (Dependence in Data an Alysis - Discussion on Some Approaches, 2005)
The paper presents the discussion on the methods of dependence analysis, where one considers continuous variables. Different criteria to systematize dependence analysis methods are proposed. The particular attention is paid to copula analysis, which is the generalization of the traditional approach to analyze linear dependence. In the paper the methods to analyze extreme dependence are also given. Finally author proposes the approach to analyze the dependence in the case of heterogeneous data set.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 48-56